L'intervention interculturelle féministe: intervenir en conciliant les enjeux interculturels et de genre - Bourassa-Dansereau, Caterine (La psychologie interculturelle en pratiques, 2019)
https://www-cairn-info.proxy.bibliotheques.uqam.ca/la-psychologie-interculturelle-en-pratiques–9782804706302.htm
Keywords: OFDIG; approches et analyses; droits des femmes*; genre; identités LGBTQIA2+; interculturalité; intervention; justice sociale; perspective théorique; pédagogie; ressource en ligne; thématiques; témoignage

La reconnaissance de l’homoparenté au Québec. Lorsque les stratégies de mobilisation de la communauté rencontrent l’avant-gardisme de l’État - Côté, Isabel; Lavoie, Kévin (Revue des politiques sociales et familiales, 2018)
Résumé Cet article retrace les jalons historiques ayant mené à l’institutionnalisation de l’homoparenté au Québec et met en lumière la synergie entre les revendications d’associations gaies et lesbiennes et les interventions étatiques de l’appareil gouvernemental. La décriminalisation de l’homosexualité au Canada en 1969, puis l’ajout de l’orientation sexuelle comme motif illicite de discrimination dans la Charte québécoise des droits et libertés en 1977 ont posé les bases juridiques sur lesquelles s’est ancrée la reconnaissance des couples de même sexe et des familles homoparentales aux tournants du nouveau millénaire. Les stratégies de mobilisation déployées par les groupes militants se sont alors inscrites dans les filières institutionnelles de l’action publique, à la rencontre des interventions progressistes de l’État québécois. L’analyse rétrospective de cette lutte offre une meilleure compréhension de la transformation des représentations familiales contemporaines et des débats actuels en matière de filiation.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; discours dominant; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; justice sociale; maternité; parentalité; premier cycle; privilèges; périodes historiques; queer; québec; régions géographiques; sciences humaines; soc2262; soc2264; sociologie; systèmes d'oppressions; thématiques

Rapport sur le racisme vécu par la communauté LGBTQ+ montréalaise - Almeida, Jade (Conseil Québécois LGBT, 2017)
Le 18 août dernier, nous avons soumis au Ministère de l’Immigration, de la Diversité et de l’Inclusion (MIDI) un projet en réponse à l’appel pour réaliser une Consultation sur le racisme systémique afin que la Commission tienne notamment compte de l’intersection entre le racisme et les LGBTphobies dans ses consultations. Notre proposition a été acceptée selon le premier mandat qui avait été choisi par le ministère. En dépit de l’évolution de ce dernier, le Conseil québécois LGBT a souhaité poursuivre la mission qu’il s’était donnée à savoir mener une consultation sur le racisme systémique en lien avec les communautés LGBTQ+. Ce document en est la synthèse. Ainsi, pour la réalisation du présent rapport, nous avons recueilli 25 témoignages individuels. Toutes les personnes interviewées ont été victimes de racisme, certaines après avoir été témoin et être intervenues. Les 25 personnes entendues font partie de la communauté LGBTQ+ et sont racisées. Autant que faire se peut, nous avons essayé de recevoir des personnes représentant une grande diversité d’identités de genres et des sexualités. Sur la totalité des témoignages, nous avons donc pu nous entretenir avec des personnes s'identifiant comme lesbiennes, trans, bisexuelles, queers, gaies, studs ou encore pansexuelles.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; homophobie; hétérosexisme; intersectionnalité; justice sociale; militance; montréal; premier cycle; périodes historiques; québec; racisme; régions géographiques; sciences humaines; sex2283; sociologie; systèmes d'oppressions; thématiques; violences

Homo inc.orporated : le triangle et la licorne qui pète - Bourcier, Sam (M.H) (Cambourakis, 2017)
Avec Homo Inc.orporated, Sam Bourcier poursuit la réflexion menée dans la trilogie des Queer Zones. Mariage, procréation, travail, patrie, les gais et les lesbiennes ont basculé dans la sphère de la reproduction et de la production. Que reste-t-il du sujet politique LGBT lorsqu'il est défini par le droit et le management de la diversité ? Pas grand-chose. Raison pour laquelle les queers et les transféministes se mobilisent pour un agenda de redistribution économique et de justice sociale plus large que la simple demande d'égalité et d'intégration. Homo Inc.orporated propose une critique radicale de l'homonationalisme et des politiques de l'égalité des droits. C'est aussi une boîte à outils pour lutter contre le néolibéralisme, avec une réflexion et de nouveaux moyens d'action sur les politiques du savoir à l'université, le genre comme travail, la grève du genre sans oublier le gender fucking !
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; approches et analyses; cours; europe; fem1000; france; identités LGBTQIA2+; justice sociale; militance; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; thématiques; transféminisme

L'homoparentalité : des familles sous le signe de la diversité - Côté, , Isabelle (2017)
Keywords: 2000 à aujourd'hui; EDI; LGBTQIA2+; amériques; approches et analyses; cours; homoparentalité; identités LGBTQIA2+; justice sociale; parentalité; premier cycle; psy4910; périodes historiques; québec; régions géographiques; santé publique; sofia; systèmes d'oppressions; thématiques

The revolution starts at home: Confronting intimate violence within activist communities - Chen, Ching-In; Dulani, Jai; Piepzna-Samarasinha, Leah Lakshmi (AK Press, 2016)
The Revolution Starts at Home is as urgently needed today as when it was first published. This watershed collection breaks the dangerous silence surrounding the “secret” of intimate violence within social justice circles. Just as importantly, it provides practical strategies for dealing with abuse and creating safety without relying on the coercive power of the state. It offers life-saving alternatives for survivors, while building a movement where no one is left behind.
Keywords: LGBTQIA2+; approches et analyses; identités LGBTQIA2+; justice sociale; militance; thématiques; violences; violences conjugales; violences contre les femmes*; violences d'état

Postures et privilèges - Institut de recherches et d'études féministes (FéminÉtudes, 2016)
Ce nouveau format de publication tend vers le livre d’artistes et illustres autant les postures féministes que ces privilèges. Postures & Privilèges, voilà un thème qui s’impose. Parce que les oppressions sont multiples; parce que les féminismes sont pluriels. Parce que les luttes tirent précisément leur force et leur vitalité de cette diversité d’expériences, de points de vue et de positionnements théoriques dans lesquels chaque féministe se construit. Et parce qu’en étant plurielles, on peut être allié.e.s et solidaires, veut-on espérer. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Disponible en libre accès : https://iref.uqam.ca/feminetudes/vol-21-no-1-2016-postures-et-privileges/
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; corps; création; cyberféminisme; féminétudes; identités LGBTQIA2+; justice sociale; maternité; militance; personnes trans*; privilèges; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; écriture des femmes*

Real queer?: sexual orientation and gender identity refugees in the Canadian refugee apparatus - Murray, David A. B. (Rowman & Littlefield International, Ltd., 2015)
An ethnographic exploration of sexual orientation and gender identity (SOGI) refugee claimants' experiences of navigating the complex discourses, protocols, practices and personnel of Canada's refugee determination system. "How do I prove I'm gay?" This is the central question for many refugee claimants who are claiming asylum on the basis of sexual orientation persecution. But what are the inherent challenges in obtaining this proof? How is the system that assesses this predicated upon homonormative frameworks and nervous borders? What is the impact of gender, race and class? What is an `authentic' sexual or gender identity and how can it be performed? Real Queer? is an ethnographic examination of the Canadian refugee apparatus analysing the social, cultural, political and affective dimensions of a legal and bureaucratic process predicated on separating the `authentic' from the `bogus' LGBT refugee. Through interviews, conversations and participant observation with various participants ranging from refugee claimants to their lawyers, Refugee Protection Division staff and local support group workers, it reveals the ways in which sexuality simultaneously disrupts and is folded into the nation-state's dynamic modes of gate-keeping, citizenship and identity-making, and the uneven effects of these discourses and practices on this category of transnational migrants
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; cours; histoire et politique; intersectionnalité; justice sociale; migration; migrations queer; premier cycle; périodes historiques; queer; régions géographiques; sex2283; système colonial; systèmes d'oppressions; thématiques

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

LGBT activism and the making of Europe: A rainbow Europe - Ayoub, Phillip; Paternotte, David (Palgrave Macmillan, 2014)
Europe has long been regarded as a unique place for the promotion and furthering of LGBT rights. This important and compelling study investigates the alleged uniqueness and its ties to a relatively long history of LGBT and queer movements in the region. Contributors argue that LGBT movements were inspired by specific ideas about European democratic values and a responsibility towards human rights, and that they sought to realize these on the ground through activism, often crossing borders to foster a wider movement. In making this argument, they discuss the 'idea of Europe' as it relates to LGBT rights, the history of European LGBT movements, the role of European institutions in adopting LGBT policies, and the construction of European 'others' in this process.
Keywords: LGBTQIA2+; activisme; approches et analyses; cours; discipline; europe; histoire; histoire et politique; identités LGBTQIA2+; justice sociale; militance; mouvements de libération; mouvements lgbtia2+; premier cycle; queer; ressource en ligne; régions géographiques; sciences humaines; sex1183; thématiques

Les oubliés du Code civil du Québec - Caron, Vincent; Berthold, Gabriel-Arnaud; Deslauriers-Goulet, Charlotte; Torres-Ceyte, Jérémie; LeBel, Louis (Les Éditions Thémis, 2014)
À l’occasion du vingtième anniversaire de l’entrée en vigueur du Code civil du Québec – événement symbolique d’importance – , il est apparu opportun d’amorcer une réflexion sur « les oubliés du Code civil », c’est-à-dire des notions qui évoluent en marge de l’œuvre codificatrice. Cet ouvrage a pour objet de faire la lumière sur certaines de ces notions dans une perspective dynamique. Ainsi, autour des principales divisions du Code civil – le droit des personnes, le droit de la famille, le droit des biens et le droit des obligations -, les auteurs offrent leurs réflexions et nourrissent un débat fertile et salutaire sur l’évolution du droit civil au Québec. Préface de Louis LeBel, juge à la Cour suprême du Canada de 2000 à 2014.
Section: xix, 226 pages ; 23 cm
Keywords: LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; droit; histoire et politique; inégalités; justice sociale; premier cycle; québec; régions géographiques; science politique et droit; soc2014; systèmes d'oppressions; thématiques

Feminist, queer, crip - Kafer, Alison (Indiana University Press, 2013)
Select all Front Matter (pp. i-vi) Front Matter (pp. i-vi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.1 Table of Contents (pp. vii-viii) Table of Contents (pp. vii-viii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.2 Acknowledgments (pp. ix-xii) Acknowledgments (pp. ix-xii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.3 Textual Description of the Cover Art (pp. xiii-xvi) Textual Description of the Cover Art (pp. xiii-xvi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.4 Introduction: Imagined Futures (pp. 1-24) Introduction: Imagined Futures (pp. 1-24) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.5 I have never consulted a seer or psychic; I have never asked a fortune-teller for her crystal ball. No one has searched my tea leaves for answers or my stars for omens, and my palms remain unread. But people have been telling my future for years. Of fortune cookies and tarot cards they have no need: my wheelchair, burn scars, and gnarled hands apparently tell them all they need to know. My future is written on my body. In 1995, six months after the fire, my doctor suggested that my thoughts of graduate school were premature, if not misguided. He... 1 Time for Disability Studies and a Future for Crips (pp. 25-46) 1 Time for Disability Studies and a Future for Crips (pp. 25-46) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.6 What would it mean to explore disability in time or to articulate “crip time”? Temporal categories are already commonly used in formulations of disability; one aspect of cripping time might simply be to map the extent to which we conceptualize disability in temporal terms. The medical field in particular has a long tradition of describing disability in reference to time. “Chronic” fatigue, “intermittent” symptoms, and “constant” pain are each ways of defining illness and disability in and through time; they describe disability in terms of duration. “Frequency,” “incidence,” “occurrence,” “relapse,” “remission”: these, too, are the time frames of symptoms, illness,... 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.7 In thinking about crip futurity, I find myself haunted by Ashley X. Born in 1997, the girl known as Ashley X was diagnosed with “static encephalopathy” a few months after her birth. “In the ensuing years,” doctors note, “her development never progressed beyond that of an infant,” and her doctors held no hope that her cognitive or neurological baseline would improve.¹ “At the age of 6 years, she [could] not sit up, ambulate, or use language.”² Concerned about their daughter’s long-term future, Ashley’s parents met with doctors in 2004 to discuss the potential effects of puberty and physical growth on... 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.8 The pervasiveness of prenatal testing, and especially its acceptance as part of the standard of care for pregnant women, casts women as responsible for their future children’s able-bodiedness/able-mindedness; prospective parents are urged to take advantage of these services so as to avoid burdening their future children with any disabilities.¹ This notion of “burdening” children finds an echo in the debate over same-sex marriage, with LGBT couples cast as selfish parents, placing their own desires over the physical and mental health of their children (and, by extension, of all children). Moreover, according to Timothy Dailey of the Family Research Council, homosexual... 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.9 “Super man,” the billboard exclaims, the unfamiliar gap between the two words emphasizing both the noun and its adjective. Below this phrase is the word “STRENGTH,” followed by the imperative “Pass It On.” At the bottom, in small print, runs the name and web address of the organization behind this public relations campaign: Values.com/Foundation for a Better Life. The “super man” referenced in the caption is, of course, the late Christopher Reeve, the white actor who starred in a series ofSupermanfilms in the 1980s before becoming a quadriplegic in a riding accident in 1995. A black-and-white photograph of... 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.10 Controversy came quickly to the cyborg. In 1983,Socialist Reviewinvited several feminist theorists, among them Donna Haraway, “to write about the future of socialist feminism in the context of the early Reagan era.”¹ Haraway responded with “A Manifesto for Cyborgs,” framing the cyborg as a figure of feminist critique.² Her cyborg was a radical border-crosser, blurring the boundaries between human and animal, machine and organism, physical and non-physical.³ Such a cyborg, she argued, could “guide us to a more livable place,” an “elsewhere,” in which “people are not afraid of their joint kinship with animals and machines, not afraid... 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.11 Although concern with the environment has long been an animating force in disability studies and activism, “environment” in this context typically refers to the built environment of buildings, sidewalks, and transportation technologies. Indeed, the social model of disability is premised on concern for the built environment, stressing that people are disabled not by their bodies but by their inaccessible environments. (The wheelchair user confronting a flight of steps is probably the most common illustration of this argument.) Yet the very pervasiveness of the social model has prevented disability studies from engaging with the wider environment of wilderness, parks, and nonhuman... 7 Accessible Futures, Future Coalitions (pp. 149-170) 7 Accessible Futures, Future Coalitions (pp. 149-170) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.12 When describing disability studies to my students, I often draw on Douglas Baynton’s insight that “disability is everywhere in history once you begin looking for it.”¹ For Baynton, “looking for it” entails not only recovering the stories of disabled people or tracing histories of disability discrimination but also exploring how notions of disability and able-mindedness/able-bodiedness have functioned in different contexts. Baynton issues his provocation to historians, but disability studies scholars in other fields have extended its reach, pushing their own colleagues to recognize disability as a category of analysis. Deeply influenced by and indebted to this work, I use this... Appendices (pp. 171-178) Appendices (pp. 171-178) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.13 Notes (pp. 179-224) Notes (pp. 179-224) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.14 Bibliography (pp. 225-252) Bibliography (pp. 225-252) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.15 Index (pp. 253-258) Index (pp. 253-258) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.16 Back Matter (pp. 259-259) Back Matter (pp. 259-259) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.17 Indiana University Press logo Front Matter Download XML Table of Contents Download XML Acknowledgments Download XML Textual Description of the Cover Art Download XML Introduction:: Imagined Futures Download XML Time for Disability Studies and a Future for Crips Download XML At the Same Time, Out of Time:: Ashley X Download XML Debating Feminist Futures:: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians Download XML A Future for Whom?: Passing on Billboard Liberation Download XML The Cyborg and the Crip:: Critical Encounters Download XML Bodies of Nature:: The Environmental Politics of Disability Download XML Accessible Futures, Future Coalitions Download XML Appendices Download XML Notes Download XML Bibliography Download XML Index Download XML Back Matter Download XML ABOUT US About JSTOR Mission and History JSTOR Labs JSTOR Daily News Webinars Careers EXPLORE CONTENT What's in JSTOR Advanced Search By Subject By Title Collections Publisher Images RESEARCH TOOLS Data for Research The JSTOR Understanding Series Constellate HELP CENTER Get Support Get Access LibGuides Research Basics Contact Us For Librarians For Publishers Teaching Resources JSTOR is part of ITHAKA, a not-for-profit organization helping the academic community use digital technologies to preserve the scholarly record and to advance research and teaching in sustainable ways.©2000‍–2024 ITHAKA. All Rights Reserved. JSTOR®, the JSTOR logo, JPASS®, Artstor®, Reveal Digital™ and ITHAKA® are registered trademarks of ITHAKA. Terms & Conditions of Use Privacy Policy Accessibility Cookie Policy Cookie Settings Description In Feminist, Queer, Crip Alison Kafer imagines a different future for disability and disabled bodies. Challenging the ways in which ideas about the future and time have been deployed in the service of compulsory able-bodiedness and able-mindedness, Kafer rejects the idea of disability as a pre-determined limit. She juxtaposes theories, movements, and identities such as environmental justice, reproductive justice, cyborg theory, transgender politics, and disability that are typically discussed in isolation and envisions new possibilities for crip futures and feminist/queer/crip alliances. This bold book goes against the grain of normalization and promotes a political framework for a more just world.
Section: xiii, 258 pages : illustrations ; 23 cm
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; care; corps; cours; crip; discipline; future; identités LGBTQIA2+; intersectionnalité; justice sociale; philosophie; premier cycle; périodes historiques; queer; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1920; thématiques; études critiques du handicap

Porno? Chic!: how pornography changed the world and made it a better place - McNair, Brian (Routledge, 2013)
Porno? Chic! examines the relationship between the proliferation of pornography and sexualised culture in the West and social and cultural trends which have advanced the rights of women and homosexuals. Brian McNair addresses this relationship with an analysis of trends in sexualised culture since 2002 linked to a transnational analysis of change in sexual politics and sex/gender relations in a range of societies, from the sexually liberalised societies of advanced capitalism to those in which women and homosexuals remain tightly controlled by authoritarian, patriarchal regimes. In this accessible, jargon-free book, Brian McNair examines why those societies in which sexualised culture is the most liberalised and pervasive are also those in which the socio-economic and political rights of women and homosexuals have advanced the most.
Section: xii, 188 p. : ill. ; 24 cm
Keywords: LGBTQIA2+; approches et analyses; communication; cours; discipline; droits des femmes*; féminisme pop; identités LGBTQIA2+; justice sociale; premier cycle; queer; sciences humaines; sciences sociales; sex1911; sexualité; thématiques; études culturelles

Identifications homosexuelles, construction identitaire et tensions postcoloniales entre le Cameroun et la France - Awondo, Patrick (L’Espace Politique, 2011)
L’article problématise la circulation de l’« identité homosexuelle » dans l’entre-deux de l’Occident et de l’Afrique. À partir de l’exemple camerounais, il montre comment des « tensions postcoloniales » parasitent le débat autour de l’homosexualité en se cristallisant notamment sur l’affrontement symbolique entre ordres moraux opposés. Au-delà des identifications sexuelles, l’analyse aborde aussi la situation des individus qui tentent par la migration d’échapper au régime de contrainte camerounais et se retrouvent dans la posture de « réfugié (homo)sexuel » en France, sans que pour autant la question de leur « identité » sexuelle soit « résolue ».
Keywords: 1900-1999; 1970-1979; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; afrique; approches et analyses; cameroun; cours; discipline; europe; france; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; inégalités; justice sociale; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

La régulation sociale des minorités sexuelles: l'inquiétude dela différence - Corriveau, Patrice; Daoust, Valérie; ProQuest (Firme) (Les Presses de l'Université du Québec, 2011)
Successivement condamnées par la religion, criminalisées par le droit pénal et finalement médicalisées, les minorités sexuelles ont subi une forte répression institutionnelle. Depuis, les luttes des mouvements gais et lesbiens ont conduit, dans certains pays, à la reconnaissance des droits des homosexuels au mariage et à la parentalité. Toutefois, l’homosexualité est encore trop souvent perçue comme une menace à la tradition et à l’ordre « naturel ». Réunissant les contributions de chercheurs en sociologie, en philosophie, en criminologie, en histoire, en anthropologie, en sexologie et en travail social, cet ouvrage porte sur les multiples modes de régulation institutionnelle et sociale des minorités sexuelles. Tout en exposant les différentes pratiques de répression employées par le passé, les auteurs traitent de sujets contemporains comme l’homophobie dans les écoles et l’homoparentalité. Soulevant des questions de justice sociale, ils rappellent que tous, gais et lesbiennes y compris, sont engagés dans le processus de régulation des minorités sexuelles.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; belgique; canada; cours; criminologie; discipline; europe; histoire; homophobie; hétérosexisme; justice sociale; militance; philosophie; premier cycle; queer; québec; régions géographiques; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; travail social; études gaies et lesbiennes

Changing the framework: Disability justice - Mingus, Mia (Leaving Evidence, 2011)
Pendant mon travail de justice sociale, j'ai découvert que le handicap est quelque chose que la plupart des gens connaissent très peu - et cela inclut des organisateurs et des militants communautaires chevronnés, féroces et très respectés. Les gens considèrent généralement le handicap comme un défaut ou un problème individuel, plutôt que comme quelque chose en partie créé par le monde dans lequel nous vivons. Il est rare que les gens pensent au handicap comme une expérience politique ou comme englobant une communauté pleine d'histoires, de cultures et d'héritages riches. .
Keywords: approches et analyses; capacitisme; corps; cours; discours dominant; fem3300; identités LGBTQIA2+; inégalités; justice sociale; personnes handicapé.e.s*; premier cycle; queer; ressource en ligne; systèmes d'oppressions; thématiques

Le prix à payer pour devenir sujet de droit: la sélection des réfugiés allosexuels au Canada - Ricard, Nathalie (Alterstice, 2011)
Depuis les années 1990, le Canada accepte des réfugiés persécutés en raison de leur orientation sexuelle. Le statut de réfugié est octroyé par les membres de la Commission de l’immigration et du statut de réfugié qui évaluent la preuve de l’orientation sexuelle et de la persécution des personnes demandant asile. Or comment prouve‐t‐on sa sexualité et sa victimisation lorsque l’on a cultivé le silence au sujet de son identité, par peur des représailles, et que le pays d’où l’on vient ne produit pas de documents au sujet de la violence homophobe ? Jusqu’à présent, l’anthropologie ne s’était pas intéressée à la question des réfugiés issus des minorités sexuelles. De leur côté, plusieurs juristes ont cherché à savoir si l’accès à l’asile était équitable pour ces personnes. Les chercheurs se sont peu attardés, toutefois, au langage du droit que ces personnes sont obligées d’utiliser pour se faire reconnaître. Cet article explore les enjeux soulevés par le témoignage des demandeurs et demandeuses d’asile issus des minorités sexuelles, en portant une attention particulière aux exigences du discours juridique qui tend à réifier les dimensions culturelles et sexuelles de la subjectivité. Ainsi, les difficultés de dire la violence ne relèveraient pas uniquement des effets traumatiques de cette dernière, mais aussi du régime d’intelligibilité de la personne qui reçoit le témoignage. Les fonctionnaires canadiens gagneraient à être sensibilisés aux différences culturelles et aux rouages de l’homophobie, à ceux de leur pays comme à ceux dans d’autres sociétés, afin que le processus asilaire soit plus équitable.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amériques; anthropologie; approches et analyses; canada; cours; discipline; droits; identités LGBTQIA2+; justice sociale; migration; minorités sexuelles; premier cycle; périodes historiques; queer; ressource en ligne; réfugiés; régions géographiques; sciences humaines; sex2283; thématiques